Corynebacterium striatum meningitis combined with suspected brain and lung abscesses: a case report and review - Zhang, Ming-Jie; Cao, Xiao-Jie; Fan, Jin; Yin, Ze-Gang; Yu, Ke (BMC infectious diseases, 2020)
Intracranial infections with Corynebacterium striatum (C. striatum) have been described sporadically in the literature over the last two decades. However, C. striatum meningitis combined with multiple abscesses has not been published before. Note that C. striatum can cause life-threatening infections. Early identification and diagnosis, early administration of antibiotics to which the bacterium is susceptible, and treatment of complications will be beneficial in patients with C. striatum-related infection.